ACUTE RENAL FAILURE - CLINICAL PRESENTING FORM OF NON-HODGKIN'S LYMPHOMA IN A HIV-POSITIVE YOUNG PATIENT - Andra Teodor; Dănuț Teodor; Gabriela Jugănariu; Codrina Bejan; Cristina-Gabriela Petrovici; Carmen Dorobăț (Romanian Society of Oral Rehabilitation, 2014)
We present the case of a woman born in 1987, identified as a HIV-seropositive at age of 11 years and classified from the beginning in AIDS-B3. She was treated with three antiretroviral regimens, her attitude being characterized by non-adherence. In 2013 she is diagnosed with diffuse large B-cell non-Hodgkin's lymphoma (plasmablastic type) and concomitantly, she presented acute renal failure with applying of hemodialysis. The patient could be affected by a wide variety of disease processes that might involve the kidney. It is difficult to distinguish an HIV-associated nephropathy accelerated by non-adherence at antiretrovirals, from an infiltrative process due to malignancy or some HAART-related renal side effects.